2017
DOI: 10.21273/hortsci11753-17
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Tomato to Potassium Rates in a Calcareous Soil

Abstract: Florida produces the most vegetables in the United States during the winter season with favorable weather conditions. However, vegetables grown on calcareous soils in Florida have no potassium (K) fertilizer recommendation. The objective of this study was to evaluate the effects of K rates on leaf tissue K concentration (LTKC), plant biomass, fruit yield, and postharvest quality of tomatoes (Solanum lycopersicum L.) grown on a calcareous soil. The experiment was conducted dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The present results are in accordance with the findings of Melendez (2012) that phosphorus helped in early flowering and fruiting. Zhu et al (2017) reported that phosphorus application to tomato plants showed increase in number of pickings plot-1. The obtained findings are in agreement with the results of Dabire et al (2016) who described that phosphorus applied to tomato plants showed more no of fruits plot-1 and no of pickings plot -1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results are in accordance with the findings of Melendez (2012) that phosphorus helped in early flowering and fruiting. Zhu et al (2017) reported that phosphorus application to tomato plants showed increase in number of pickings plot-1. The obtained findings are in agreement with the results of Dabire et al (2016) who described that phosphorus applied to tomato plants showed more no of fruits plot-1 and no of pickings plot -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Zekri and Obreza (2002) stated that the process of photosynthesis of the plant dropped severely that resulted in smaller fruit when provided with low concentrations of NPK therefore, the growth of plant was stunted and reduced fruits were formed. Zhu et al (2017) revealed that with the application of higher rates of NP fertilizers, maximum average tomato fruit weight can be achieved. In contradiction, Majanbu et al (1985) found no response due to phosphorus fertilization to pod weight of okra.…”
Section: Discussionmentioning
confidence: 99%